IMPORTANCE OF WATER FOR LIVING ORGANISMS AND NATIONAL ECONOMY, PHYSICAL AND CHEMICAL METHODS OF WASTEWATER TREATMENT - Maxmudov Rafiq Amonovich, Niyozov Sobir Ahror o‘g‘li; Sulaymonova Iroda Hamza qizi (American Journals Publishing, 2023)
Water erodes mountain systems made of hard rocks. When the water between the rocks freezes, it expands the cracks and cracks even the granite and basalts. Water slowly erodes the minerals contained in the rocks, dissolves them and carries them to the valleys. Nowadays, keeping water clean is one of the problems of serious concern to all mankind. What is the average amount of water needed for Uzbekistan per year? To answer this question, we will analyze the data on the use of water resources in various sectors of the economy in Uzbekistan
Keywords: Most of the world's fresh water is stored in the Antarctic,. It is impossible to imagine the weather of a place without atmospheric waters, It should be noted that an average person consumes 58 kg of rice per year.